Anesthesia with mask free sleep inducing balloon in pediatric patients; A tertiary care hospital experience - Azad, Abul Kalam; Haque, Mozibul; Islam, Aminul (Journal of Bangladesh College of Physicians and Surgeons, 2020)
Introduction: Children are habitually frightened and become combative during the induction of anesthesia. It is challenging for pediatric anesthesiologists to minimize psychological upset by reducing scaring environment of operating room and to facilitate a smooth induction of anesthesia. Use of force to handle severely anxious and scared children may lead to postoperative behavioral problems. Purpose: There is an immense need to develop a simple device to ensure mask free and stress-less induction for children. Sleep Inducing Balloon is the mask-free and stress-less anesthesia delivery system designed for children which is not only fulfilling the criteria of ideal breathing system but also replaces anxiety with amusement and fear with fun! Methods: A study was conducted among 100 children between 6 months to 7 years of age, during the period of Apr 2018 to Dec 2018 to find out the induction time of Sleep Inducing Balloon who were scheduled for elective short surgical procedure under general anaesthesia having ASA grading I and II. While doing so, children receive constant gas mixture of 5L oxygen mixed with 5% sevoflurane till fall asleep. Results: A total 100 patients were included in this study to record induction time, heart rate and oxygen saturation to validate the function of Sleep Inducing Balloon. Mean age of the children was 3.50±1.04 years, mean weight was 10.7±3.24 Kgs and mean heart rate was 120±8.3/min. Most of the children had ASA grade-I (96%) and oxygen saturation was 99%. Induction time was 60-80 seconds in 26% patients, and 81-100 seconds in 45% of the children. In 24% children the induction time was 101-120 seconds, 5% children took more than two minutes for induction. There was no failure and adverse events were easy to manage. Conclusion: Mask free sleep inducing balloon is a safe and successful way of anesthetic induction in pediatric patients. The procedure ensures a stress-free peaceful event in frightened children. J Bangladesh Coll Phys Surg 2021; 39(1): 19-23